Fruit and vegetable intake and pancreatic cancer risk in a population‐based cohort study in Japan. Issue 8 (30th October 2018) - Yamagiwa, Yoko; Sawada, Norie; Shimazu, Taichi; Yamaji, Taiki; Goto, Atsushi; Takachi, Ribeka; Ishihara, Junko; Iwasaki, Motoki; Inoue, Manami; Tsugane, Shoichiro
Abstract : Oxidative stress and chronic inflammation are potential pathogenic factors of pancreatic cancer. Although fruits and vegetables are abundant in antioxidants and anti‐inflammatory constituents, the reported associations between fruit and vegetable intake and pancreatic cancer risk have been inconsistent. Here, we investigated the association between fruit and vegetable intake and pancreatic cancer risk as part of the Japan Public Health Center‐based Prospective Study. The analysis included 90, 185 participants who responded to a medical and lifestyle questionnaire during 1995–1998. Associations between fruit and vegetable intake and pancreatic cancer risk were evaluated with Cox proportional hazards models. Additional analyses were stratified by smoking status and body mass index. During follow‐up (median duration, 16.9 years), 577 participants were diagnosed with pancreatic cancer. In multivariate‐adjusted models, pancreatic cancer risk was inversely associated with total fruit intake (highest vs . lowest intake quartile; hazard ratio [HR]: 0.74, 95% confidence interval [CI]: 0.57–0.95, p ‐trend: 0.116) and positively associated with total vegetable intake (HR: 1.30, 95% CI: 1.01–1.66, p ‐trend: 0.151). For total fruit intake, the inverse association with pancreatic cancer risk was more apparent in never smokers (HR: 0.67, 95% CI: 0.47–0.97, p ‐trend: 0.034). For total vegetable intake, the positive association was statistically significant in ever smokers (HR: 1.49, 95% CI: 1.01–2.19, p ‐trend: 0.043) and statistically nonsignificant in never smokers. In summary, total fruit intake and total vegetable intake had inverse and positive associations, respectively, with pancreatic cancer risk. Vegetable intake may correlate with increased risk partly because of the influence of smoking on vegetable intake. Abstract : What's new? Oxidative stress and chronic inflammation are potential pathogenic factors of pancreatic cancer. Possible causes of oxidative stress and chronic inflammation including chronic pancreatitis, diabetes mellitus, obesity, and smoking are all risk factors. Although fruits and vegetables are abundant in antioxidants and anti‐inflammatory constituents, the reported associations between fruit and vegetable intake and pancreatic cancer risk have been inconsistent, however. In this prospective Japanese study, pancreatic cancer risk was inversely associated with total fruit intake and positively associated with total vegetable intake. The association between vegetable intake and pancreatic cancer risk was observed in ever smokers, but not in never smokers.